2011
DOI: 10.1016/j.febslet.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of microRNA‐375 and its role in melanoma development in humans

Abstract: Edited by Tamas Dalmay Keywords:Epigenetic regulation MicroRNA miR-375 Cell invasion Human melanoma a b s t r a c tTo identify epigenetically regulated miRNAs in melanoma, we treated a stage 3 melanoma cell line WM1552C, with 5AzadC and/or 4-PBA. Several hypermethylated miRNAs were detected, one of which, miR-375, was highly methylated and was studied further. Minimal CpG island methylation was observed in melanocytes, keratinocytes, normal skin, and nevus but hypermethylation was observed in patient tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 39 publications
(56 reference statements)
1
68
1
Order By: Relevance
“…21 In addition, miR-375 was significantly downregulated in liver cancer cell lines and hepatocellular carcinoma tissues, and overexpression of miR-375 in liver cancer cells was associated with decreased cell proliferation, clonogenicity, invasion and migration. 26 In another study, miR-375 was identified as one of the most pronounced markers for tumour progression in patients with prostate cancer.…”
Section: Microrna-375 In Human Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition, miR-375 was significantly downregulated in liver cancer cell lines and hepatocellular carcinoma tissues, and overexpression of miR-375 in liver cancer cells was associated with decreased cell proliferation, clonogenicity, invasion and migration. 26 In another study, miR-375 was identified as one of the most pronounced markers for tumour progression in patients with prostate cancer.…”
Section: Microrna-375 In Human Nsclcmentioning
confidence: 99%
“…Poy et al 20 reported that overexpression of miR-375 could suppress glucose-induced insulin secretion independently of changes in transmembrane Ca 2+ fluxes or glucose metabolism. Emerging evidence has also shown associations between decreased miR-375 expression and tumourigenesis and progression in melanoma, 21 carcinoma of the head and neck, 22 and pancreatic, 23 oesophageal, 24 29 The Medical Ethics Committee of Xiangya Hospital approved this study and all patients provided written informed consent prior to undergoing surgery.…”
Section: Microrna-375 In Human Nsclcmentioning
confidence: 99%
“…16,17,[23][24][25][26][27][28][29][30][31][39][40][41][42] Downregulation of miR-375 has been reported for gastric cancer, cervical cancer, pancreatic ductal adenocarcinoma and hepatocellular carcinoma. 26,27,29,30,[43][44][45] In gastric cancer, ectopic expression of miR-375 in cancer cells reduced cell viability and induced apoptosis by targeting PDK1 and tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein z (YWHAZ).…”
Section: Aberrant Expression Of Mir-375 and Its Target Genes In Othermentioning
confidence: 99%
“…16,17 Other research groups also showed downregulation of miR-375 in HNSCC and ESCC and other types of human cancers. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] In this review, we focus on HNSCC and ESCC and describe the aberrant expression of miRNAs in these cancers and the cancer pathways they may regulate in these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…They are also known to control various aspects of transcriptional and post-transcriptional mRNA processing, and may further regulate mRNA function by binding and masking key elements within the coding sequence. Examples are elements that may be required for the binding of trans-acting factors in post-transcriptional gene expression, such as splicing, transport, translation and degradation of pre-mRNA [8]. Non-coding RNAs are also transcribed by mechanisms similar to those involved in the transcription of most protein-coding genes, and therefore, not surprisingly, abnormal regulation of non-coding RNA genes may induce prostate cancer development and progression in humans.…”
Section: Introductionmentioning
confidence: 99%